Motivation to Learn from the Perspective of the Qur'an - Salman Yafi; Ikhwan Rahman; Ramadhanul Ikhsan; Ulfatmi (Saniya Institute, 2023)
Students' motivation to learn is currently declining. This can be seen from their low academic grades and their behavior in learning activities which is indicated by laziness and not paying attention to the teacher when teaching. This study uses the literature review method which allows a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and the relevance in the field / against a research result.In the field of education, there is no doubt that the existence of the Qur'an has influenced the education system. By studying the Koran, it can provide inspiration and motivation in all aspects of life. Obtained Quranic verses related to motivation, namely QS. al-Mujadalah: 11, QS. al-Kahf: 66-67, QS. al-'Alaq: 1-5, QS. al-Nahl: 78, QS. al-Luqman: 17-19, and al-Ra'd: 11. By understanding the Quranic messages on motivation to learn, students can explore spiritual wisdom and apply it in their journey to learn and understand the universe.